MODEL KOOPERATIF TIPE PICTURE AND PICTURE DALAM PEMBELAJARAN - Hayati, Rahmatul; Prima, Wahyu (Dharmas Education Journal (DE_Journal), 2023)
Image media is one of the effective media to use in learning because it can attract students' attention in learning. For this reason, it is necessary to apply a learning model that uses image media as its main support, including the picture and picture cooperative learning model. The purpose of this study was to examine the effect of the picture and picture cooperative learning model. The method used is a literature study that collects several references from previous studies. Data analysis techniques in this study used descriptive analysis. Sources of data in this study came from several main references, namely fifteen scientific papers. The results of the analysis show that the picture and picture cooperative learning model can improve learning outcomes, activeness, and student learning motivation. The results of this study are an initial study in the development of electronic learning media based on the Picture and Picture Type Cooperative learning model, so that learning is meaningful for students and according to student needs.